JMY protein, a regulator of P53 and cytoplasmic actin filaments, is expressed in normal and neoplastic tissues. - Adighibe, O; Turley, H; Leek, R; Harris, A; Coutts, A; La Thangue, N; Gatter, K; Pezzella, F (Springer Verlag, 2014)
JMY is a p300-binding protein with dual action: by enhancing P53 transcription in the nucleus, it plays an important role in the cellular response to DNA damage, while by promoting actin filament assembly in the cytoplasm; it induces cell motility in vitro. Therefore, it has been argued that, depending of the cellular setting, it might act either as tumor suppressor or as oncogene. In order to further determine its relevance to human cancer, we produced the monoclonal antibody HMY 117 against a synthetic peptide from the N-terminus region and characterized it on two JMY positive cell lines, MCF7 and HeLa, wild type and after transfection with siRNA to switch off JMY expression. JMY was expressed in normal tissues and heterogeneously in different tumor types, with close correlation between cytoplasmic and nuclear expression. Most noticeable was the loss of expression in some infiltrating carcinomas compared to normal tissue and in in situ carcinomas of the breast, which is consistent with a putative suppressor role. However, as in lymph node metastases, expression of JMY was higher than in primary colorectal and head and neck carcinomas, it might also have oncogenic properties depending on the cellular context by increasing motility and metastatic potential.